2008
DOI: 10.1627/jpi.51.298
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Photo-antioxidant Activities of Chalcone Derivatives

Abstract: Chalcones are the starting materials for the biosynthesis of flavonoids. Flavonoids are strong antioxidants, which contain many phenolic hydroxyl group(s). However, the antioxidant activities of chalcones have been little studied. In this study, chalcones with chemical structures resembling natural chalcones were synthesized, and the effects of the hydroxyl group(s) on the A and B rings and the C3 chain connecting the A and B rings were investigated in detail. Hydroxyl group(s) on the B ring inherited the char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 2 publications
2
24
0
Order By: Relevance
“…The identification was done with Fourier transform-infrared spectroscopy (FT-IR) and 1 H-nuclear magnetic resonance (NMR Other materials, such as solvents, azo-bis-isobutyronitrile (AIBN), hydroquinone, catechol and resorcinol, 3,5-di-t-butyl-4-hydroxytoluene (BHT), and 2-hydroxybenzophenone (2-HBP) were purified by conventional methods. 2',4-Dihydroxychalcone was prepared according to the procedure described in a previous paper 3) .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The identification was done with Fourier transform-infrared spectroscopy (FT-IR) and 1 H-nuclear magnetic resonance (NMR Other materials, such as solvents, azo-bis-isobutyronitrile (AIBN), hydroquinone, catechol and resorcinol, 3,5-di-t-butyl-4-hydroxytoluene (BHT), and 2-hydroxybenzophenone (2-HBP) were purified by conventional methods. 2',4-Dihydroxychalcone was prepared according to the procedure described in a previous paper 3) .…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the present study revealed that the first metabolite, p-coumaric acid, shows higher radical-scavenging activity than the commercial antioxidant, BHT. p-Coumaric acid is further metabolized to a chalcone, which also acquires high photo-antioxidant activity 3) . Chalcones are present only in small amounts, probably due to their instability in plants, and are metabolized to a stable flavonoid, naringenin.…”
Section: Antioxidant and Photo-antioxidant Activities Along The Metabmentioning
confidence: 99%
See 2 more Smart Citations
“…Chalcones (1,3-diphenyl-2-propene-1-ones) either natural or synthetic have been reported to posses varieties of biological activities [1] including anticancer, 2 antimitotic, 3 antiinflammatory, 4 antimalarial, 5 antiangiogenic, 6 antiinfective, 4j antimicrobial, 7 antioxidative, 2f-g, 8 and antiproliferative 9 activities. Similarly, flavanones (2,3-dihydro-2-phenylchromene-4-one) have also been reported to posses anticancer, 10 antimicrobial, 11 antiproliferative, 9b antiinflammatory, 10a cardiovascular, 10a antimalarial, 5c,12 antiangiogenic, 6 and hypotensive 11b activities.…”
Section: Introductionmentioning
confidence: 99%